Women's common destiny maternal representations in the serialized Cebuano fiction of Hilda Montaire and Austregelina Espina-Moore - Yu, Hope Sabanpan 1964- (The University of the Philippines Press, 2009)
In this first ever book-length study of maternal representations in Cebuano literature, Hope Sabanpan-Yu reveals the confluence of indeginous and foreign cultures and convincingly connects the theory of split-level maternity to the debate on motherhood in the Philippines. As women's participation in social and economic affairs grew, Yu argues, so too did the social significance of their maternal relations.